Analysis to Establish Differences in Efficiency Metrics Between Operating Room and Non-Operating Room Anesthesia Cases. - Wu, Albert; Sanford, Joseph; Tsai, Mitchell; O'Donnell, Stephen; Tran, Billy; Urman, Richard (Journal of Medical Systems, 2017)
While a number of studies have examined efficiency metrics in the operating rooms (ORs), there are few studies addressing non-operating room anesthesia (NORA) metrics. The standards established in the realm of OR studies may not apply to ongoing investigations of NORA efficiency. We hypothesize that there are significant differences in these commonly used metrics﻿. Using retrospective data from a single tertiary care hospital in the 2015 calendar year, we measured turnover times, cancellation rates, first case start delays, and scheduling error (actual time minus scheduled time) for the OR and NORA settings. On average, TOTs for NORA cases were approximately 50% shorter than OR cases (16.21 min vs. 37.18 min), but had a larger variation (11.02 min vs. 8.12 min). NORA cases were 64% as likely to be cancelled compared to OR cases. In contrast, NORA cases had an average first case start delay that was two times greater than that of OR cases (24.45 min vs. 10.58 min), along with over double the standard deviation (11.97 min vs. 5.90 min). Case times for NORA settings tended to be overestimated (−4.07 min versus −2.12 min), but showed less variation (8.61 min vs. 17.92 min). In short, there are significant differences in common efficiency metrics between OR and NORA cases. Future studies should elucidate and validate appropriate efficiency benchmarks for the NORA setting.